Underneath the Radar: Emergency search and rescue insurance for East Antarctic tourism - Julia Jabour (2007)
Operators of tourism activities in the Antarctic will soon be legally required to hold adequate insurance for emergency search and rescue. This may push some operators underground because they cannot afford to pay. The intent of the new law is to encourage compliance with tourism best practice and self-sufficiency. In the East Antarctic, maritime search and rescue is problematic due to limitations on the response capability. When Australia and New Zealand implement this law they may make provision for cost recovery, otherwise the insurance requirement is meaningless. However, cost recovery overlaps with obligations they have under the SAR Convention to provide emergency search and rescue as a maritime community service, foregoing cost recovery.